The power of equivocation : complex readers and readings of the Hebrew Bible - Kalmanofsky, Amy (Minneapolis : Fortress Press, 2022)
The Power of Equivocation reveals the complexity inherent in biblical narratives, particularly those featuring female characters, and models a way of reading that enables critical-religious interpreters to straddle their dual identities and loyalties and read the Bible critically, generously, and honestly.
Equivocal readings of the Hebrew Bible: an introduction from an equivocal reader -- Potiphar's wife and Joseph -- Hannah -- Saul, Samuel, Hannah, and the woman from En-dor -- Esther and Mordecai -- Tamar and Judah -- Bathsheba, David, and Solomon -- Unequivocal conclusions from an equivocal reader.
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Reading; Bible. -- Biography; Bible; Women in the Bible; Feminism -- Religious aspects -- Judaism; Criticism, interpretation, etc